Pengaruh Persepsi Pengetahuan, Pemahaman dan Implementasi Akuntansi terhadap Penggunaan Sistem Informasi Akuntansi pada UKM di Kecamatan Metro Timur - Salsabila, Zamira; Darmayanti, Elmira Febri; Fitriani, Fitriani (Universitas Muhammadiyah Metro, 2023)
Perceptions of UKM actors about accounting, accounting knowledge, accounting understanding, and accounting implementation affect the use of accounting information systems. This type of research is quantitative research. The population of this study is all UKM in the Metro City of 8.211 with a sample of 110 respondents. Data analysis techniques used are descriptive statistics, classical assumption test and hypothesis test. The results of the research on The perception of UKM actors about accounting, accounting knowledge, accounting understanding, and accounting implementation has a positive and significant.